Biomechanical comparison of different uphill techniques in the classical style cross-country skiing - Andersson, E.; Stöggl, T.; Pellegrini, B.; Sandbakk, O.; Holmberg, H. C. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: Over the last decade a new sprint technique has emerged, the diagonal running (DIA-run) technique. This technique differs from diagonal stride (DS) due to the absence of the gliding phase and therefore resembles running. It is regularly used in sprint races for acceleration and high speed diagonal skiing. No previous study has biomechanically compared the DIA-run with the DS or herringbone (HB) techniques on snow. Hence, the aims of the present study were to examine the kinematics and kinetics that differentiate the techniques, as well as performance.